Physical Activity and Risk of Obesity Among Urban Preadolescents - Point of Concern During Pandemic - M, CHITRA (Indian Journal of Integrative Medicine, 2022)
Childhood obesity is an emerging risk factor for cardiovascular morbidity and mortality in the future. Hormonal activity during preadolescent period along with other modifiable factors like environmental, social and physical can have a profound effect on the physical, physiological and psychological growth of Preadolescent. Physical activity during childhood period is a measure of energy expenditure that helps in active growth of the child. During the pandemic period, extensive lifestyle changes and sedentary behavior has forced many children to remain physically inactive. Children exhibit low level of physical activity in the recent years. High calorie binge eating and sedentary lifestyle coupled with hormonal changes predispose to vicious cycle of obesity related disorders among urban preadolescents. Promoting physical activity by using gadgets and school initiatives for fitness during lockdown helps to monitor childhood obesity at an early age.